A loop‐mediated isothermal amplification (LAMP) assay based on unique markers derived from genotyping by sequencing data for rapid in planta diagnosis of Panama disease caused by Tropical Race 4 in banana. (20th October 2019) - Ordóñez, N.; Salacinas, M.; Mendes, O.; Seidl, M. F.; Meijer, H. J. G.; Schoen, C. D.; Kema, G. H. J.
Abstract : The socio‐economic impact of Fusarium odoratissimum, which is colloquially called tropical race 4 (TR4), is escalating as this fungal pathogen spreads to new banana‐growing areas. Hence, the development of simple, reliable and rapid detection technologies is indispensable for implementing quarantine measures. Here, a versatile loop‐mediated isothermal amplification (LAMP) assay has been developed that is applicable under field and laboratory conditions. DNA markers unique to TR4 isolates were obtained by diversity arrays technology sequencing (DArTseq), a genotyping by sequencing technology that was conducted on 27 genotypes, comprising 24 previously reported vegetative compatibility groups (VCGs) and three TR4 isolates. The developed LAMP TR4 assay was successfully tested using 22 TR4 isolates and 45 non‐target fungal and bacterial isolates, as well as on infected plants under greenhouse and field conditions. The detection limit was 1 pg µL −1 pure TR4 DNA or 10 2 copies plasmid‐localized TR4 unique sequence (SeqA) per reaction, which was not affected by background DNA in complex samples. The LAMP TR4 assay offers a powerful tool for the routine and unambiguous identification of banana plants infected with TR4, contributing to advanced diagnosis in field situations and monitoring of fusarium wilt.